Parapapillary Atrophy: Histological Gamma Zone and Delta Zone - Jonas, Jost B.; Jonas, Shefali B.; Jonas, Rahul A.; Panda-Jonas, Songhomitra (PLOS ONE, 2012)
Background: To examine histomorphometrically the parapapillary region in human eyes. Methodology/Principal Findings: The histomorphometric study included 65 human globes (axial length:21-37 mm). On anterior-posterior histological sections, we measured the distance Bruch's membrane end (BME)-optic nerve margin (“Gamma zone”), BME-retinal pigment epithelium (RPE) (“Beta zone”), BME-beginning of non-occluded choriocapillaris, and BME-beginning of photoreceptor layer. “Delta zone” was defined as part of gamma zone in which blood vessels of at least 50 µm diameter were not present over a length of >300 µm. Beta zone (mean length:0.35±0.52 mm) was significantly (P = 0.01) larger in the glaucoma group than in the non-glaucomatous group. It was not significantly (P = 0.28) associated with axial length. Beta zone was significantly (P = 0.004) larger than the region with occluded choriocapillaris. Gamma zone (mean length:0.63±1.25 mm) was associated with axial length (P<0.001;r2 = 0.73) with an increase starting at an axial length of 26.5 mm. It was not significantly (P = 0.24) associated with glaucomatous optic neuropathy. Delta zone (present only in eyes with axial length of ≥27 mm) was associated with axial length (P = 0.001) and scleral flange length (P<0.001) but not with glaucoma (P = 0.73). Conclusions/Significance: Parapapillary gamma zone (peripapillary sclera without overlying choroid, Bruch's membrane and deep retinal layers) was related with axial globe elongation and was independent of glaucoma. Delta zone (no blood vessels >50 µm diameter within gamma zone) was present only in highly axially elongated globes and was not related with glaucoma. Beta zone (Bruch's membrane without RPE) was correlated with glaucoma but not with globe elongation. Since the region with occluded choriocapillaris was smaller than beta zone, complete loss of RPE may have occurred before complete choriocapillaris closure.